Formulation of Moringa oleifera Lam. based Bio-fortified Food Supplement for Pregnant Women in Madagascar, Indian Ocean - Randrantoarimbola Lazaniriana; Rafalimanantsoa Jules; Ratiarimananjatovo Narindra; Randriamanantena A. Andrin’iranto; Ngiala Bongo; Koto-te-Nyiwa Ngbolua; Robijaona Baholy (Britain International for Academic Research (BIAR) Publisher, 2020)
The pregnant woman feeding is very important for the optimal embryonic development of the zygote. The present study suggests a formulation of food supplement in soup form. We were able to make a soup which is composed of vegetables and animal products. This product like food supplement can cover the pregnancy nutrients needs. In fact, the nutrients deficiencies during the first 1000 days lead to chronic malnutrition. Hence, preventive actions concerning this nutritional plague are necessary. Among that, the food supplement for pregnant manufacture can compensate the micronutrients and protein-energy deficiencies. This animal and plant-based food supplement contains various minerals such as Mg (368 mg/100g DM); Ca (2003 mg/100g DM); K (1324 mg/100g DM); P (204 mg/100g DM); Cu (0, 57 mg/100g DM); Fe (28, 2 mg/100g DM). Besides, the product is composed by carbohydrates (38, 2 g/100g DM), fats (2, 3 g/100g DM), and proteins (27, 1 g/100g DM) fibers (19, 3 g/100 g DM). It energetic value is 205 kCal per 100g.